Possible ameliorative effects of kolaviron against reproductive toxicity in sub-lethally whole body gamma-irradiated rats (2010)
Ionizing radiation is one of the environmental factors that may contribute to reproductive dysfunction by a mechanism involving oxidative stress. We investigated the possible ameliorative effects of kolaviron (KV) (a biflavonoid from the seeds of Garcinia kola) on sperm characteristics, testicular lipid peroxidation (LPO) and antioxidant status after a whole body _-irradiation in Wistar rats. Vitamin C (VC) served as standard antioxidant in this study. The study consists of four groups of 6 rats each. Group I received corn oil, whereas group II received a single dose of _-radiation (5 Gy). The animals in groups III and IV were pretreated with KV (250 mg/kg) and VC (250 mg/kg) by oral gavage five times in a week, respectively, for 6 weeks prior to and 8 weeks after exposure to _-radiation. Gamma-irradiation resulted in a significant (p < 0.05) decrease in body weight and relative testes weight. Also, _-irradiation significantly (p < 0.05) decreased the activities of superoxide dismutase, catalase and glutathione S-transferase as well as glutathione level, but markedly elevated malondialdehyde levels in the serum and testes. Irradiated rats showed testicular degeneration with concomitant decrease in sperm motility and viability. Although sperm abnormalities significantly increased, it has no effect on the epididymal sperm count. KV and VC significantly (p < 0.05) decreased the body weight loss and increased relative testes weights of the rats. Furthermore, supplementation of KV and VC ameliorated radiation-induced toxicity by increasing the activities of antioxidant enzymes, decreased LPO and abrogated testicular degeneration. Taken together,_-irradiation caused reproductive dysfunction by depleting the antioxidant defence system in the rats, while administration of KV or VC ameliorated the radiation-induced testicular toxicity.